Republished paper: The WHO patient safety curriculum guide for medical schools. Issue 1026 (31st March 2011) - Walton, Merrilyn; Woodward, Helen; Van Staalduinen, Samantha; Lemer, C; Greaves, F; Noble, D; Ellis, B; Donaldson, L; Barraclough, B; ,
Abstract : Background: The urgent need for patient safety education for healthcare students has been recognised by many accreditation bodies, but to date there has been sporadic attention to undergraduate/graduate medical programmes. Medical students themselves have identified quality and safety of care as an important area of instruction; as future doctors and healthcare leaders, they must be prepared to practise safe healthcare. Medical education has yet to fully embrace patient safety concepts and principles into existing medical curricula. Universities are continuing to produce graduate doctors lacking in the patient safety knowledge, skills and behaviours thought necessary to deliver safe care. A significant challenge is that patient safety is still a relatively new concept and area of study; thus, many medical educators are unfamiliar with the literature and unsure how to integrate patient safety learning into existing curriculum. Design: To address this gap and provide a foothold for medical schools all around the world, the WHO's World Alliance for Patient Safety sponsored the development of a patient safety curriculum guide for medical students. The WHO Patient Safety Curriculum Guide for Medical Schools adopts a 'one-stop-shop' approach in that it includes a teacher's manual providing a step-by-step guide for teachers new to patient safety learning as well as a comprehensive curriculum on the main patient safety areas. This paper establishes the need for patient safety education of medical students, describes the development of the WHO Patient Safety Curriculum Guide for Medical Schools and outlines the content of the Guide.